A socio-economic transformation of the ECER-development programmes in enhancing the well-being of the people - Abdul Rahman Abdul Latip; Norfatiha Othman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Just and sustainable socio-economic development is an important indicator in achieving Sustainable Development Goals (SDG). In 2007, the states in the east coast of Peninsular Malaysia were among the states with the highest poverty rate in Malaysia. East Coast Economic Region (ECER) that has been established in 2008 is an economic development region based on the east coast of Peninsular Malaysia, covers Kelantan, Terengganu, Pahang and the district of Mersing in Johor. The ECER Master Plan, approved by the Government in 2008, was formulated as a basis to guide the development of ECER until 2025 to reduce regional socio-economic disparities, eradicating poverty, creating employment opportunities and improving the standard of living for the local populace. This study aims to analyse the socio-economic transformation brings by ECER into this region in the aspects of job creation, investment, and entrepreneurship opportunities. The study uses the qualitative approach (in-depth interviews) with 10 key informants including direct observation, as well as library research. The informants comprised of five informants from the policy making level, and the remaining five informants from the implementation level. NVivo software used to analyse the qualitative data. The finding of this study finds positive transformations of the ECER development programmes towards the region in terms of investment, job creation, and entrepreneurship opportunities. It is hope that ECER will continue to facilitate the socio-economic transformation of this region towards becoming a developed region by 2025.